Monitoring and Analysis of Single Tube Temperature Distribution in Heat Exchanger Simulator Using TPA 81 Thermopile Array - Murry Raditya; Gunawan Nugroho; Abdurrahman Rahyang Tutuko; Halen Dinata Atmaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The Energy and Environmental Engineering Laboratory had a heat exchanger simulator which was used to determine the temperature changes with respect to time due to air velocity. This simulator used tubes which were used to find out the temperature change with time. The working principle of this simulator was to monitor changes in temperature on the tube that had been preheated and then cooled using a fan contained in the simulator. This study performed temperature measurements using a TPA81 thermal array sensor. We chose this sensor because it could measure the temperature without touching the object and had 8 pixels for image measurement. This was because the process of reducing the temperature of the tube becomes purely caused by the fan and not from the outside environment. The results obtained from this study were visualization of temperature distribution using the Thermal Array TPA81 sensor, having a linearity value of 0.034%, a precision value of the instrument of 98.1%, an accuracy value of 0.285%, and error value of 0.154 (W/m2K). For the analysis of temperature distribution, it was concluded that the value of the temperature did not affect the value h, because the value of h (the coefficient of heat transfer convection) is distributed with time.